Sanitising business : fraud and ethics. (Managerial Auditing Journal., 2002)
The purpose of this study is to determine ifmembers of the Institute of ManagementAccountants (IMA) use the IMA Code ofEthics in recognizing and resolving ethicaldilemmas. This is important for severalreasons. First, membership in the IMA andadherence to its code of ethics are largelyvoluntary.